AN ERROR ANALYSIS ON THE USE OF PAST TENSE IN NARRATIVE TEXTS - Maria Dewi Rosari; Yobel Caesar Sianturi (PROJECT (Professional Journal of English Education), 2023)
Errors committed in grammar can impair communication performance in both speaking and writing.  Therefore, grammar is significantly essential; however, many English learners still misuse it. The research was conducted to identify students’ errors in using simple past tense in the narrative text. Error analysis was a chosen method to find out the formulated research problems. To analyze the errors committed by students, the researchers used strategy taxonomy by Dulay and Krashen (1982), namely omission, addition, misordering, and misformation. The researchers found that misformation was the most dominant type of error committed by the students, with an occurrence frequency of 65.94%. Meanwhile, the occurrence frequency of other types of errors is as follows:  omission with 30.76%, addition with 2.20%, and the last is misordering with 1.10%. Equally important, the researchers also identified the factors influencing the most dominant error from the perspective of second language acquisition. The researchers found three contributing factors, namely past tenses acquisition and aspects, the interference of Indonesian grammar habits, and the absence of English tenses in Indonesian. Recommendation for further researchers and English learners and teachers are discussed further in the last section. Keywords:  Grammar; Past Tense; Error Analysis; Narrative Text; Second Language Acquisition